Market discipline and the use of government bonds as collateral in the EMU - Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
The confidence that financial markets are able to discipline the debt behaviour of governments is not very high. Therefore, the Stability and Growth Pact has been implemented as an institutional constraint to substitute for the market mechanism. With the weakening of the Pact, market discipline could gain importance again. To strengthen market discipline, reasons for its failure in the euro area have to be analysed. One possible reason could be that the European Central Bank accepts all European government bonds without distinction in its monetary policy auctions as collateral. This could provide the financial market with a signal that these government securities are equally (non-)risky and that a differentiation with respect to risk premia is not needed.
Keywords: H63; G12; E52; E51; 330; Stability and Growth Pact; Market Discipline; Collateral; Repo